Nickel–zinc sulfide nanocomposite thin film as an efficient cathode material for high-performance hybrid supercapacitors. (January 2020) - Kaliaraj, Gobi Saravanan; Ramadoss, Ananthakumar
Abstract: Nickel–Zinc Sulfide nanocomposite (Ni–ZnS) thin film was prepared by RF magnetron co-sputtering method on a stainless steel substrate, which is used as the cathode material for hybrid supercapacitor. The as-prepared Ni–ZnS nanocomposite thin films exhibit a hexagonal structure with uniform morphology. The electrochemical results show that the Ni–ZnS nanocomposite thin film electrode exhibited a higher specific capacity when compared to the ZnS thin film. The Ni–ZnS-3 electrode has the highest specific capacity of 134 C g −1 (67 mC cm −2 ) at a scan rate of 10 mV s −1 with excellent cycling stability (10% loss of its initial specific capacity) even after 3500 cycles. The obtained results reveal that nickel doping has the significant effect on the electrochemical performance of zinc sulfide material and the as-fabricated material can be used as a potential positive electrode for hybrid supercapacitors. Graphical abstract: Image 1